2017
DOI: 10.2807/1560-7917.es.2017.22.19.30530
|View full text |Cite
|
Sign up to set email alerts
|

Increasing proportion of carbapenemase-producing Enterobacteriaceae and emergence of a MCR-1 producer through a multicentric study among hospital-based and private laboratories in Belgium from September to November 2015

Abstract: Carbapenemase-producing Enterobacteriaceae (CPE) strains have been increasingly reported in Belgium. We aimed to determine the proportion of CPE among Enterobacteriaceae isolated from hospitalised patients and community outpatients in Belgium in 2015. For the hospitalised patients, the results were compared to a previous similar survey performed in the same hospitals in 2012. Twenty-four hospital-based and 10 private laboratories collected prospectively 200 non-duplicated Enterobacteriaceae isolates from clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 22 publications
2
25
1
1
Order By: Relevance
“…The Greek situation differs greatly from other European countries such as Spain, France, Germany, Turkey, Romania and Belgium, where OXA-48, most often linked with community-onset healthcare associated sources, is the most frequently encountered carbapenemase [26,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 97%
“…The Greek situation differs greatly from other European countries such as Spain, France, Germany, Turkey, Romania and Belgium, where OXA-48, most often linked with community-onset healthcare associated sources, is the most frequently encountered carbapenemase [26,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 97%
“…It is important to know the local prevalences of OXA-48 and OXA-48-like ␤-lactamases among clinical isolates so that infections caused by isolates with a higher MIC value for a carbapenem, even if the MIC does not cross the threshold of "resistant," should be considered for treatment options other than carbapenems. Therapeutic options available for treating infections caused by carbapenem-resistant Enterobacteriaceae are often limited to older agents, often with impaired safety profiles, such as aminoglycosides, tigecycline, fosfomycin, and polymyxins (8); in this light, recent reports of colistin-resistant OXA-48-producing isolates are very concerning (67)(68)(69)(70). This study also showed an increased incidence of colistin resistance in OXA-48-producing isolates, with 21.3% of the isolates being nonsusceptible to colistin, compared to only 17% for all Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, plasmid-mediated resistance (mediated by mcr genes) was discovered (292). While the association between mcr genes and carbapenemase production is anecdotal so far (293)(294)(295)(296)(297)(298), the association of these genes with successful mobile genetic elements or clones, together with the use of colistin in veterinary and human medicine leading to increased selection pressure, is a cause for concern. Furthermore, susceptibility testing with colistin is problematic: broth microdilution methods are recommended because diffusion tests are not reliable (66), and semiautomated methods may cause very major errors (as explained at http://www.eucast.org/ast_of_bacteria/ warnings/ [accessed 22 October 2017]).…”
Section: Polymyxinsmentioning
confidence: 99%